Eosinophilic Gastrointestinal Disorders: Unravelling the Complexities of a Rare Entity - Jose, Neethu; M, Akshatha; B S, Girish; H C, Bharath Gowda (Indian Journal of Pharmacy Practice)
Eosinophilic ascites is a rare manifestation of serosal eosinophilic gastrointestinal disease. We present case of a 61-year-old female k/c/o Hypothyroidism who presented with eosinophilic ascites and was managed with tapering doses of steroids. Awareness of the condition, timely diagnosis, and early treatment carries excellent responses. This case highlights the importance of considering eosinophilic ascites in the differential diagnosis of unexplained ascites and underscores the need for a comprehensive diagnostic approach to identify the underlying cause.
Keywords: Eosinophilic Esophagitis; Eosinophilic Gastrointestinal Disease; Clinical Scenario; Eosinophilic ascites